Principles for Online Teaching/Emergency Remote Delivery - Wride, Michael; Centre for Academic Practice and Student Learning (TCD) (Trinity College Dublin, The University of Dublin, 2020)
A list of principles/guidelines for the production of online teaching/emergency remote delivery produced by CAPSL in the context of the COVID-19 shutdown.
Keywords: Instructional design, principles